Laparoscopic approach of a spontaneous vesico-ovarian fistula in an infected endometriotic cyst: an atypical presentation - Yogini, Kavitha; Maran, Varsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Spontaneous vesico-ovarian fistula is a sporadic occurrence. It can either occur as a result of a large abscess draining into the bladder or due to spontaneous fistula secondary to deep infiltrative endometriosis which might get contaminated with urine. Impaired immunity and bloody content of the endometrioma may facilitate the formation of tubo-ovarian abscess in endometriosis. This case report deals with a case of tubo-ovarian abscess with spontaneous vesico-ovarian fistula managed by minimally invasive surgery. A 40-year-old, parous lady presented with an incidental finding of endometriotic cyst with no associated symptomatology at our outpatient department. Hence, patient was planned for ovarian suppression with GnRH analogues. While on her second dose, patient had complaints of lower abdominal pain, dysuria and pyuria. On further evaluation, MR imaging was suggestive of bilateral tubo-ovarian abscess. Patient was planned for laparoscopic management of tubo-ovarian abscess. Intra-operative findings were suggestive of a frozen pelvis with frank pus draining in the urobag. Cystoscopy was done, suggestive of vesico-ovarian fistula involving the dome of the bladder. Trans-mesenteric drainage of the ovarian abscess was done, and patient was started on broad spectrum antibiotics which was culture sensitive. TB-PCR was negative for this patient. Catheterization for 3 weeks aided in the spontaneous healing of the fistula. Her final histopathology was suggestive of infected endometriosis. After suppression, with 2 doses of GnRH analogues, patient was planned for definitive surgery. MR imaging in endometriosis yields more information when the ultrasound is unclear, in cases of deep infiltrative endometriosis and in cases where surgery is planned as it provides larger field of view and better contrast resolution. Asymptomatic endometriosis if untreated might increase the risk of tubo-ovarian abscess, hence timely management is mandatory. An atypical presentation of tubo-ovarian abscess is noted in this report unlike other abscesses. Here, in our case, laparoscopic hysterectomy was done after the primary surgery of TOA drainage due to residual tubo-ovarian abscess and persisting endometriosis. Tubo-ovarian abscess can have varying presentation. Endometriosis is considered to be a risk factor for the development of tubo-ovarian abscess, hence timely diagnosis and management is necessary. Pre-operative MR imaging and laparoscopic approach with a multidisciplinary team in such cases would aid in decreased post-operative morbidity and quick recovery.